Long-Term Outcomes With Adalimumab Therapy in Pediatric Crohn Disease: Associations With Adalimumab Exposure. Issue 3 (30th March 2022) - Rinawi, Firas; Popalis, Cynthia; Tersigni, Claudia; Frost, Karen; Muise, Aleixo; Church, Peter C.; Walters, Thomas D.; Ricciuto, Amanda; Griffiths, Anne M.
ABSTRACT: Background/Aims: Pediatric Crohn disease (CD) treatment goals have evolved. Among children receiving adalimumab (ADA) we examined long-term durability of clinical remission, linear growth, and associations of trough concentration (TC) with biomarker, endoscopic and imaging outcomes. Methods: Single-center retrospective study. Pediatric CD activity index, C-reactive protein, fecal calprotectin, and height measured longitudinally. Discontinuation due to secondary loss of response (LOR) was assessed using Cox proportional hazards model. Associations between TC and clinical and biomarker remission, endoscopic and magnetic resonance imaging (MRI) improvements were assessed using Cox regression with time-dependent covariates. Results: Between January 2007 and June 2018, 213 children (median age 14.1 years (interquartile range [IQR] 12.5–15.7) 65% males) initiated ADA. One hundred and seventy-four (82%) achieved clinical remission (PCDAI < 10). During 24.8 (IQR 15.6–38.4) months follow-up, 26 (15%) discontinued ADA due to LOR, and 10 (6%) due to adverse events. Being anti-tumor necrosis factor (TNF) naïve and inflammatory behavior associated with increased likelihood of clinical remission (odds ratio [OR] 2.39, P  = 0.033, and 3.13, P  = 0.013, respectively) and with decreased LOR (hazard ratio [HR] 0.3, P  = 0.002, and HR 0.35, P  = 0.01, respectively). Cumulative LOR among 135 anti-TNF naïve patients: 0%, 8%, 15% within 1, 2, 3 years, similarly durable with mono- and immunomodulator combination therapy. Among pre-/early pubertal children mean height (−0.82) normalized to −0.07. TC consistently >7.5 ug/mL was associated with durable clinical remission (HR = 17.24, P  < 0.001); TC >10 ug/mL with durable biomarker remission (HR = 6.56, P  < 0.001) and endoscopic (OR 10.4, P  = 0.002) and MRI (OR 7.6, P  = 0.001) improvements. Conclusion: ADA monotherapy maintains durable clinical remission. Biomarker remission, mucosal and transmural improvements were associated with greater ADA exposure.